Understanding hormone and hormone therapies' impact on the auditory system. Issue 9 (5th February 2020) - Williamson, Tanika T.; Zhu, Xiaoxia; Pineros, Jennifer; Ding, Bo; Frisina, Robert D.
Abstract: Hormones such as estrogen, progesterone, and aldosterone all demonstrate vital roles in sustaining auditory function through either the maintenance of cochlear neurons, up/down regulation of critical molecules (i.e., IGF‐1, BDNF, etc.), or generation of the endocochlear potential. With disease and/or age, hormone expression begins to decline drastically, which ultimately affects cochlear structures and the integrity of cochlear cells. The following review explores the latest findings as well as realistic outcomes for hormone therapy treatment in the auditory system. This information could serve as a potential guide for patients considering hormone therapy as a medicinal choice to alleviate the signs of onset of presbycusis—age‐related hearing loss. Additional scientific investigations could also be carried out to further enhance recent findings.